2012
DOI: 10.1063/1.3694280
|View full text |Cite
|
Sign up to set email alerts
|

Hydration strongly affects the molecular and electronic structure of membrane phospholipids

Abstract: We investigate the structure and electronic properties of phosphatidylcholine (PC) under different degrees of hydration at the single-molecule and monolayer type level by linear scaling ab initio calculations. Upon hydration, the phospholipid undergoes drastic long-range conformational rearrangements which lead to a sickle-like ground-state shape. The structural unit of the tilted gel-phase PC appears to be a water-bridged PC dimer. We find that hydration dramatically alters the surface potential, dipole and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…The dipole moment is ∼10 D, several fold larger than the dipole moment of a water molecule. 15,28 Electric field-induced enhancement of water dissociation has been experimentally observed previously using field emitter tips where the surface electric fields are estimated to be on the order of 1 V/Å. 27 Fields of this magnitude distort molecules, induce ionization and break bonds, and thus lead to an increased dissociation constant of interfacial water.…”
Section: −25mentioning
confidence: 99%
See 4 more Smart Citations
“…The dipole moment is ∼10 D, several fold larger than the dipole moment of a water molecule. 15,28 Electric field-induced enhancement of water dissociation has been experimentally observed previously using field emitter tips where the surface electric fields are estimated to be on the order of 1 V/Å. 27 Fields of this magnitude distort molecules, induce ionization and break bonds, and thus lead to an increased dissociation constant of interfacial water.…”
Section: −25mentioning
confidence: 99%
“…The electronic properties and vibrational eigenmodes of the above structures, i.e., pure and hydrated DPPC samples, are reported in our two most recent works 15,16 Generally speaking, obtaining a negative (imaginary, because what is obtained is actually ω 2 rather the ω) frequencies is a signature of having an unstable structure that is energetically very sensitive to small changes in atomic positions. It has been shown that apart from three, and only three, frequencies with |ω| < 0.1 cm −1 (corresponding to three acoustic modes), all the other eigenfrequencies (total 390 eigenfrequencies for pure, 570 for DPPC/(H 2 O) 20 , and 840 for DPPC/(H 2 O) 50 ) are positive.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations